Strategi Pengembangan Usaha Gambir Rakyat Menggunakan Analisa SWOT di Kabupaten Pesisir Selatan - Khairul Fahmi; Rahimullaily Rahimullaily (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The demand of gambier’s commodity increases continuously through the year. However, many problems that were faced by gambier’s farmers in its cultivation, processing, and marketing. This research aims to identify the main problem which affect the development of the gambier’s business in South Pesisir district and to find out the model and the strategy of gambier business development in south Pesisir district. This is qualitative research by using SWOT analysis to collect the data. The SWOT analysis is used to analyze and to find out the strategy of gambier business development. The result of this research shows that the problems that are faced by gambier’s farmers in south pesisir district are very complex; including various aspects, for example marketing, capital, technology, organization and the main problem is the dependency of the gambier farmers to the middleman. The strategies recommendations of that problems are partnership and industry clusters approaches.Keywords: Strategy; Gambir; Business Development; SWOT AbstrakPermintaan terhadap komoditas gambir terus meningkat sepanjang tahun. Namun demikian, sampai saat ini masih banyak permasalahan yang dihadapi petani gambir dalam budidaya, pengolahan, dan pemasarannya. Penelitian ini bertujuan mengidentifikasi persoalan utama yang mempengaruhi pengembangan usaha gambir di Kabupaten Pesisir Selatan serta menemukan strategi dan model pengembangan usaha gambir di Kabupaten Pesisir Selatan. Pengumpulan data menggunakan metode penelitian kualitatif dengan menggunakan analisis SWOT untuk menganalisis dan menemukan strategi pengembangan usaha gambir. Hasil penelitian ini menunjukkan bahwa persoalan yang dialami petani gambir di Pesisir Selatan sangat kompleks meliputi berbagai aspek seperti pemasaran, permodalan, teknologi dan kelembagaan serta persoalan yang paling pokok adalah adanya ketergantungan petani gambir terhadap penampung/ toke. Rekomendasi strategi dari persoalan tersebut adalah pendekatan kluster industri dan kemitraan.Kata Kunci: Strategi; Gambir; Pengembangan Usaha; SWOT